Effects of temperature and superparasitism on quality and characteristics of thelytokous Wolbachia-infected Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) during mass rearing - Zhou, Jin-Cheng; Li, Yuan-Yuan; Liu, Quan-Quan; Ning, Su-Fang; Che, Wu-Nan; Cong, Bin; Dong, Hui (Scientific reports, 2019)
Thelytokous Wolbachia- infected Trichogramma spp. are widely used egg parasitoids against lepidopteran pests in biological control programs. Wolbachia may manipulate host wasps for superparasitism and is sensitive to temperature. To explore effects of temperature and superparasitism, we compared fitness parameters and Wolbachia -mediated phenotype of thelytokous Wolbachia -infected Trichogramma dendrolimi between those emerging from superparasitised or single-parasitised hosts at 17, 21, 25, or 29 °C. Infected mothers of T. dendrolimi showed reduced superparasitism and parasitism increased with temperature. Wolbachia titre decreased with temperature when females emerged from singly-parasitised hosts, but there was no correlation in superparasitised hosts. Females showed higher Wolbachia titres at 21, 25, or 29 °C when developing from superparasitised hosts. The daily male ratio of offspring increased with temperature, and the day-age threshold for 5%, 50%, or 95% daily male ratio decreased with temperature in both parasitism forms. Females that emerged from superparasitised hosts had a shorter life span and reduced fecundity. These results indicate that Wolbachia may affect host behaviour by increasing superparasitism to enhance its spread, but this has negative effects on thelytokous Wolbachia -infected T. dendrolimi .